Aplikasi Pemantauan dan Peringatan Dini untuk Energi Baru Terbarukan Berbasis Android dengan Restful Api (Studi Kasus Kajian EBT Polinema dan PT. PLN - Yuniari, Nilam; Ed Dien, Habibie; Ariyanto, Rudy (Politeknik Negeri Malang, 2024)
Renewable energy sources are environmentally friendly energy sources, because they do not cause environmental changes and do not cause climate change and global warming. Due to the influence of astronomy and geography, Indonesia is a country that is rich in potential new and renewable energy sources such as geothermal energy, solar, water, wind, marine and bioenergy. In the context of providing sustainable electricity, PT. PLN is collaborating with the Malang State Polytechnic to increase the use of renewable energy to become a power plant that utilizes kinetic energy and solar energy. In the development process, monitoring of power plants is currently still done manually. Monitoring the condition of power plants will be more effective and efficient if it is done automatically. Technological trends that support these applications are now starting to increase, especially on smartphones with the Android operating system. From a standalone application, it has now turned into an application that can be connected to other applications using a global network known as Restful API and is integrated with Internet of Things (IoT) technology which can monitor the condition of generators in real time and provide emergency information. Therefore, there is a need for applications that can assist in the process of developing power plants that can monitor and provide early warning notifications. The system designed and implemented uses a MySQL database and the Java programming language in the Android Studio application. From the test results using a Likert Scale, a feasibility percentage of 86.5% of users stated that the application was in accordance with its function and was able to make it easier for users, namely admins, operators, stakeholders, asset managers, project owners and PLN in monitoring EBT generators.